2021
DOI: 10.5664/jcsm.9168
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Withings Sleep Analyzer, an under-the-mattress device for the detection of moderate-severe sleep apnea syndrome

Abstract: Study Objectives: To assess the diagnostic performance of a nonintrusive device placed under the mattress to detect sleep apnea syndrome. Methods: One hundred eighteen patients suspected to have obstructive sleep apnea syndrome completed a night at a sleep clinic with a simultaneous polysomnography (PSG) and recording with the Withings Sleep Analyzers. PSG nights were scored twice: first as simple polygraphy, then as PSG. Results: Average (standard deviation) apnea-hypopnea index from PSG was 31.2 events/h (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 37 publications
2
61
1
Order By: Relevance
“…This requires further investigation. Nonetheless, recognizing these potential caveats, published validation data (16) and our own validation assessment (online supplement) show reasonably good agreement in AHI quantified via the under-mattress device compared to in-laboratory polysomnography.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This requires further investigation. Nonetheless, recognizing these potential caveats, published validation data (16) and our own validation assessment (online supplement) show reasonably good agreement in AHI quantified via the under-mattress device compared to in-laboratory polysomnography.…”
Section: Discussionmentioning
confidence: 74%
“…These signals are used to estimate sleep macrostructure (total sleep time), sleep timing (bedtime and wake-time) and the AHI using automated algorithms (see supplementary material for a more detailed technology description). Clinical validation shows good agreement with polysomnography-derived AHI (16,17) with high predictive performance (88% sensitivity and 88% specificity) to classify moderate-to-severe OSA (≥15 events/h sleep). A further internal validation study in 32 participants (26 men and 6 women) independently studied at the Adelaide Institute for Sleep Health laboratory (see Supplementary Material), showed similar diagnostic performance characteristics.…”
Section: Monitoring Equipmentmentioning
confidence: 80%
See 1 more Smart Citation
“…Nasal cannula and thermistor cannot measure inspiratory effort, and nasal cannula cannot measure mouth breathing. Though, there are also other nonwearable alternatives like using sound [24] (subject to audio noise from surroundings), visionbased solutions (affected by bed sheets), infrared solutions [25], or under-the-mattress solutions [26,27]. To the authors' knowledge, neither of these alternatives has been shown to reliably classify individual sleep apnea type, apnea duration, or temporal distribution of events.…”
Section: Discussionmentioning
confidence: 96%
“…At a second home visit, the participants were equipped with the wearable Withings Steel HR smartwatch (Withings Inc), tracking the number of steps and heart rate on a per-minute basis. Participants were also equipped with the nearable Withings Aura sleep mattress (Withings Inc), tracking the various phases of sleep (sleep onset latency, wake, light sleep, deep sleep, rapid eye movement [REM] sleep, and waking up times) on a per-minute basis [ 34 ]. The first day of data logging for the participants spanned from June 7, 2017, to September 25, 2017.…”
Section: Methodsmentioning
confidence: 99%